ТӘБИЯТ ҲӘМ ЖӘМИЙЕТ ҚАТНАСЫҚЛАРЫНДА ҚОРШАҒАН ОРТАЛЫҚТАҒЫ ЭКОЛОГИЯЛЫҚ МАШҚАЛАЛАРДЫӉ КЕСКИНЛЕСИЎ ЖАҒДАЙЛАРЫ - Нурланов, А.С. (ILIM hám JÁMIYET, 2023)
The consequence of drying the Aral Sea is negatively influencing to the deterioration of the ecolocial crisis upon changing natural ambiences and especially to all branches of public facilities in the Republic of Karakalpakstan. In the article mentioned the importance of using rationally natural sources and the affects of ecological crisis to the surrounding.